PKM GURU SENI RUPA/KERAJINAN SMP KOTA PARIAMAN DAN SMPN KABUPATEN PADANG PARIAMAN DALAM PEMBELAJARAN KERAJINAN TENUN KARTU - Syafwan Syafwan; Irwan Irwan; Erwin Erwin; Zubaidah Zubaidah; Sri Novi Restari (Ranah Seni, 2019)
Arts and skills / craft education is a set of knowledge that can be used by teachers to train and awaken aesthetic sensitivity so that they can experience the knowledge and experience gained in everyday life (Pakasi, 2007: 60). Thus, the results of arts education and skills are expected to increase the ability to apply, develop, and disseminate art in an effort to improve the level of social life and enrich the culture of society. Based on observations and discussions of the community service team with teachers in the fields of Fine Arts and Skills in several Pariaman City Middle Schools (December 12, 2018) that, most teachers do not teach skills learning. That is, demands for competency standards, especially learning of skills do not run accordingly. While the framework for developing curriculum for Junior High School / Madrasah Tsanawiyah workshops must be directed at developing skills at the level of manipulation (modification) aimed at producing multi-design products from both basic material types and product forms based on the potential of local wisdom. One of the efforts that can be done is to help teachers of arts and culture and skills to develop insights and skills in learning crafts, namely Weaving Card Crafts with various types of materials and techniques for products of disposable objects and art objects. This card weaving craft training is packaged in the Community Partnership Program (PKM) which is very useful for art and skills teachers to be taught to students according to the demands of the 2013 curriculum "to appreciate and be able to make local-based handicraft works", because not all students are able continuing higher education, they must be equipped with skills in school.